Primary and Secondary Postgraduate Students’ Ways of Selecting Courses and Encountered Problems - Kurnaz, Mehmet Altan; Alev, Nedim (Journal of Turkish Science Education, 6(3), 38-52, 2009)
Duty of preparing scientists which is among basic missions of universities starts with accepting individuals to the post-graduate education after they graduated from an undergraduate programme. In general, basic aims of post-graduate education are to educate qualified human power; such as, scientists and lecturers, to produce works which lead to developments in technical field, and to do research devoted to finding or proposing solutions to basic problems (Sevinç, 2001). Selecting postgraduate students for Doctorate or Master Programmes requires certain criteria. It is accepted that these criteria effect the quality of the process of educating scientists (Çıkrıkçı-Demirtaşlı, 2002). The quality of this process depends on students’ approaches and their academic experiences in each stage of the process as well as their selection. Postgraduate programmes can be considered as a process consisting of three substages: beginning, research and writing (URL-1). Beginning stage, in this classification, can be described as a preparatory phase for students to prepare themselves for the research stage which includes the process of executing the study and drawing conclusions from the study, and writing stage, on the other hand, is the phase of writing the report of the study. These stages should be considered as parallel processes rather than follow-ups. However, it is widely accepted that the beginning stage is the cornerstone of the whole process. One thing for doing this as it deserves is to select and take certain courses that would make contributions to the preparation for research area. However, little has been done to guide young researchers on how they select or would select courses that are more useful for thier future works. Thus, it is believed that this study would make a contribution to the reader, directors of Master and Doctorate programme, post-graduate students and others, to reflect on their acts.
Keywords: Post-graduate Education; Courses in Post-graduate Education; Course Election , Approaches.